Statistical processing of pharmacological experiments results measured in ordinal and quantitative scales, if it is impossible to analyze using parametric methods - I. B. Tsorin (LLC "Publisher OKI", 2021)
The article discusses descriptive statistics of data measured in ordinal and quantitative scales, and criteria for determining the statistical significance of differences between samples when it is impossible to analyze using parametric methods. Special attention is paid to the problem of multiple comparisons of this type of data. For each method, examples of processing data obtained in pharmacological studies are given.